2020
DOI: 10.3389/fpls.2020.01140
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel Phenotypic Roadmap to Improve Blueberry Quality and Storability

Abstract: Improved fruit quality and prolonged storage capability are key breeding traits for blueberry (Vaccinium spp.) fruit. Until now, breeding selection was mostly oriented on the amelioration of agronomic traits, such as flowering time, chilling requirement, or plant structure. Up until now, however, the storage effect on fruit quality has not been extensively studied, mostly because objective and handy phenotyping tools to evaluate quality traits were not available. In this study we are proposing a novel phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…Six of the identified aroma-active monoterpenoids were only found in fruit of one of the five cultivars. Other studies reported differences in monoterpenoid composition among cultivars [ 14 , 19 , 33 , 34 , 35 , 36 ], and it was suggested that differences in monoterpenoid content could be responsible for the distinct aroma of different blueberry cultivars as well as consumer acceptability [ 14 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six of the identified aroma-active monoterpenoids were only found in fruit of one of the five cultivars. Other studies reported differences in monoterpenoid composition among cultivars [ 14 , 19 , 33 , 34 , 35 , 36 ], and it was suggested that differences in monoterpenoid content could be responsible for the distinct aroma of different blueberry cultivars as well as consumer acceptability [ 14 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The use of advanced molecular tools to facilitate breeding for economically important traits including FQ rely on the characterization of the existing blueberry germplasm 1 3 , 11 and the study of the genetic mechanisms controlling these traits. Multiple studies demonstrated significant phenotypic variability for FQ traits within blueberry germplasm, and the traits have also shown moderate to high genetic heritability 1 3 , 11 , 20 , 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Ethylene content was additionally estimated on powdered frozen material by setting the SRI-ToF-MS in H 3 O + mode (PTR-ToF-MS mode, Cappellin et al, 2014;Busatto et al, 2022). According with the recent publication about the application of a highthroughput methodology to assess blueberry VOC profile based on PTR-ToF-MS (Farneti et al, 2020), we analyzed the possibility to apply that methodology to measure ethylene, together with all other VOCs. Three replicates of 0.5 g of powdered frozen sample, each obtained by three fruit, were inserted into 20 ml glass vials equipped with PTFE/silicone septa (Agilent, Cernusco sul Naviglio, Italy) and mixed with 0.5 ml of deionized water, 200 mg of sodium chloride, 2.5 mg of ascorbic acid, and 2.5 mg of citric acid (Farneti et al, 2020).…”
Section: High Throughput Assessment Of Ethylene On Powdered Frozen Ma...mentioning
confidence: 99%
“…According with the recent publication about the application of a highthroughput methodology to assess blueberry VOC profile based on PTR-ToF-MS (Farneti et al, 2020), we analyzed the possibility to apply that methodology to measure ethylene, together with all other VOCs. Three replicates of 0.5 g of powdered frozen sample, each obtained by three fruit, were inserted into 20 ml glass vials equipped with PTFE/silicone septa (Agilent, Cernusco sul Naviglio, Italy) and mixed with 0.5 ml of deionized water, 200 mg of sodium chloride, 2.5 mg of ascorbic acid, and 2.5 mg of citric acid (Farneti et al, 2020). Sample headspace was withdrawn through SRI-ToF-MS (in H 3 O + mode) inlet with 40 ml min −1 flow for 60 cycles resulting in an analysis time of 60 s/sample.…”
Section: High Throughput Assessment Of Ethylene On Powdered Frozen Ma...mentioning
confidence: 99%